Effect of Emotional Intelligence on Delinquents in KPK - Iqbal, Hina; Shafiq, Mohammed; Khayam,; Naseer , Rabia (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims at assessing the effect of Emotional intelligence (EI) on delinquents in KPK. For this, a sample of 200(n) adolescents were selected which is comprised of 100(n) Delinquents, selected from Jail of Peshawar and Haripur whereas 100(n) non- delinquents who were selected from different schools of Peshawar and Haripur by keeping age and other demographic same. Before collecting the data on EI, their delinquency was evaluated on Self-Reported Delinquency Scale (SRD) and categorized them into delinquents and non-delinquent’s groups respectively. It was hypothesized that delinquents have impaired EI than non-delinquents. The second hypothesis was to investigate the effect of EI on delinquency. By using the independent sample t-test, delinquents scored significantly low on all the subscales of EI i.e., Emotional self- Acceptance (ESA), Emotional self-Regulation Scale (ESRS) and Interpersonal skills (ISS) AND (p